Single-chamber microbial electrosynthesis reactor for nitrate reduction from waters with a low-electron donors’ concentration: from design and set-up to the optimal operating potential - Lust, Rauno; Nerut, Jaak; Gadegaonkar, Sharvari S.; Kasak, Kuno; Espenberg, Mikk; Visnapuu, Triinu; Mander, Ülo (Frontiers in Environmental Science, 2022)
Microbial electrosynthesis is a promising solution for removing nitrate from water with a low concentration of electron donors. Three single-chamber microbial electrosynthesis reactors were constructed and operated for almost two years. The single-chamber reactor design saves on construction costs, and the pH of the solute is more stable than in case of a two-chamber reactor. Nitrate reduction started at the working electrode potential of −756 mV vs standard hydrogen electrode (SHE), and subsequently, the working electrode potential could be raised without hindering the process. The optimal potential was −656 mV vs SHE, where the highest Faradaic efficiency of 71% and the nitrate removal rate 3.8 ± 1.2 mgN-NO3/(L×day) were registered. The abundances of nitrite reductase and nitrous oxide reductase genes were significantly higher on the working electrode compared to the counter electrode indicating that the process was driven by denitrification. Therefore, microbial electrosynthesis reactor was successfully applied to remove nitrate and can be utilized for purifying water when adding organic compounds as electron donors is not feasible, i.e. groundwater. In addition, at the lower working electrode potentials, the dissimilatory nitrate reduction to ammonium was observed.